2005
DOI: 10.1002/ptr.1671
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Toki-shakuyaku-san on amyloidβ25-35-induced neuronal damage in cultured rat cortical neurons

Abstract: Amyloid beta protein (Abeta) is the major component of senile plaques, the pathological hallmark of the neurodegeneration associated with Alzheimer's disease (AD). This study investigated the effect of Toki-shakuyaku-san (TSS), a traditional medicine, on Abeta25-35-induced neuronal death and lipid peroxidation assessed by measuring lactate dehydrogenase (LDH) and malondialdehyde (MDA), respectively. Abeta25-35 at 10 microM induced neuronal damage and increased the LDH and MDA. TSS at concentrations of 100 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…DSS inhibited Aβ25-35-induced neuronal damage and lactate dehydrogenase (LDH). The Aβ25-35-induced neuronal death and lipid peroxidation were significantly reduced by DSS at concentrations of 100 and 300 µg/mL [63]. Through DSS administration, the SCOP-induced impairment including reference and working memory deficits of a rat's spatial cognition determined in the eightarmed radial maze test was decreased [65].…”
Section: Figure 1 Dss-mediated Resolution Of Aβ In Alzheimer's Diseasementioning
confidence: 88%
“…DSS inhibited Aβ25-35-induced neuronal damage and lactate dehydrogenase (LDH). The Aβ25-35-induced neuronal death and lipid peroxidation were significantly reduced by DSS at concentrations of 100 and 300 µg/mL [63]. Through DSS administration, the SCOP-induced impairment including reference and working memory deficits of a rat's spatial cognition determined in the eightarmed radial maze test was decreased [65].…”
Section: Figure 1 Dss-mediated Resolution Of Aβ In Alzheimer's Diseasementioning
confidence: 88%
“…For more than thousand years, DSS has been used to improve post-menopausal disorders with neurological symptoms, and regulate hypothalamic-pituitary-endocrine system and immune-neuroendocrine functions in China (Kou et al, 2005;Goto et al, 2009). Recently, many studies have showed that DSS had therapeutic efficacy for senile dementia by enhancing the cognitive behavior (Kou et al, 2002;Hatip-AI-Khatib et al, 2004;Hu et al, 2010), improving the mitochondrial impairment (Kou et al, 2005) and inhibiting neuronal damage (Egashira et al, 2005;Qian et al, 2008;Hwang et al, 2011). These abovementioned findings provide some pharmacological basis for the dementia prevention function of DSS.…”
Section: Introductionmentioning
confidence: 96%
“…In animal studies, DJS improves spatial cognition impairment (Egashira et al, 2004), central cholinergic nervous system dysfunction (Itoh et al, 1996), and A␤-induced spatial recognition deficits (Hu et al, 2010). DJS also has neuroprotective effects in hydrogen peroxide-induced toxicity in PC12 cells (Qian et al, 2008), A␤ 25-35 -induced neuronal damage in cultured rat cortical neurons, and senile dementia in aged mice (Egashira et al, 2005).…”
Section: Introductionmentioning
confidence: 97%